Keadilan Restoratif Sebagai Paradigma Baru Dalam Pembaruan Hukum Pidana Indonesia (Harmoniasasi Dan Konvergensi Dengan Hukum Islam) - Zulpahmi Lubi; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Restorative justice as a new paradigm in the reform of Indonesian criminal law emphasizes the restoration of relationships between the perpetrator, the victim, and the community, rather than mere retribution. This approach shifts the focus from retribution to reconciliation and social healing. This article examines the relationship between restorative justice and Islamic legal principles that emphasize the protection of life, honor, and property. The harmonization of both offers a more balanced and humane perspective on justice. In the philosophical dimension, restorative justice opens up space for substantial justice that takes into account social, moral, and spiritual aspects, and directs the reform of Indonesia's criminal law towards an approach of restoration and social peace.